Pengaruh NPL, LDR, dan BOPO Terhadap ROA Bank BUMN yang Terdaftar di BEI Tahun 2018-2020 - Indri Fitriyanti; Gusganda Suria Manda (Jurnal Ilmiah Wahana Pendidikan, 2022)
The role of banking in this time is very influential on the financial system. Even today's banks also have a very important role to support economic progress in Indonesia. A good financial system will have a positive impact on financial performance. This study aims to find out the influence of Banking Risk analyzed using NPL, LDR, BOPO to ROA Ratio of STATE-OWNED Banks. The data used in this study, obtained from the financial statements of state-owned banks listed on the Indonesia Stock Exchange. The number of bank samples examined is 4 state-owned banks registered with idx in the period 2018-2020. This study uses the spss method where the results show that simultaneously, NPL, LDR, and BOPO have a significant effect on ROA. And partially, NPL is significant and negatively affects ROA, LDR is insignificant and negatively affects ROA, BOPO is significant and negatively affects ROA. Through this research it is known that banking risk measured through three existing ratios has a significant influence on financial performance (ROA). State-owned banks should be able to identify the risks that may occur in their business activities. With regard to the results of research where the company must minimize NPL, LDR and BOPO ratio because it negatively.